Pathological Lung Ultrasound May Take Time to Resolve Despite Respiratory Symptoms Improvement: A Pediatric Case Series Followed for Long COVID - Klain, Angela; Indolfi, Cristiana; Dinardo, Giulio; Contieri, Marcella; Decimo, Fabio; Miraglia del Giudice, Michele (Current Respiratory Medicine Reviews, 2023)
Background: Long COVID affects 8 to 10 % of children. Currently, the COVID-19 follow- up protocols in children include chest auscultation, collection of growth parameters, including weight, height and body mass index, execution of the six-minute walking test, basal spirometry, and afterwards, bronchodilation test and lung ultrasound.Case Presentation: In this paper, the authors describe a case series of long COVID followed up for 9 months at the Department of Pediatrics of the University Luigi Vanvitelli. The review of the literature was performed on PubMed using the keywords COVID-19, follow-up, children, and lung ultrasound. The aim of this article was to highlight the need to create custom follow-up programs for long Covid in children through the description of a case followed up at our Pediatric Department and a review of the current literature.Discussion: The reversal of pathological lung ultrasound signs occurred in six or nine months despite the early improvement of respiratory symptoms and pulmonary function. There are limited studies on the ultrasonography follow-up of kids with COVID-19 in the literature, and there are still no follow-up COVID-19 guidelines for paediatric population.Conclusion: Pathological lung ultrasound in children recovered from COVID-19, may take time to resolve; therefore, evaluating patients with lung ultrasound in the following months could be a radiation- saving approach useful for children who have fully recovered and have no warning signs.
Keywords: Case series